PEMANFAATAN KECERDASAN BUATAN SEBAGAI ASISTEN GURU DALAM PERENCANAAN PEMBELAJARAN SEKOLAH DASAR - Budi Raharjo; Asep Nurjen (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Learning planning is a fundamental aspect of the implementation of teaching and learning in elementary schools, as it directly affects the quality of the learning process and student learning outcomes. In the implementation of the Deep Learning Curriculum, elementary school teachers are required to design learning plans that are flexible, contextual, and student-centered. However, in practice, teachers still face challenges such as limited time and a high administrative workload. The development of Artificial Intelligence (AI) offers new opportunities to be utilized as a teaching assistant in learning planning. This study aims to describe the utilization of artificial intelligence as a teacher assistant in elementary school learning planning, as well as teachers’ perceptions of its ease of use and usefulness. The research method employed was a descriptive survey involving elementary school teachers as participants. The research instrument was a questionnaire measuring aspects of ease of use and the perceived usefulness of AI in learning planning. The results indicate that the use of AI helps teachers more efficiently formulate learning objectives, teaching modules, and assessment tools. Teachers perceive AI as a supportive tool that assists their professional tasks without replacing their pedagogical role. This study concludes that artificial intelligence has the potential to become an effective assistant for elementary school teachers in learning planning.